Association of spontaneous bleeding and myocardial infarction with long-term mortality after percutaneous coronary intervention - Kazi, Dhruv S; Leong, Thomas K; Chang, Tara I; Solomon, Matthew D; Hlatky, Mark A; Go, Alan S (Journal of the American College of Cardiology, 2015)
Platelet inhibition after percutaneous coronary intervention (PCI) reduces the risk of myocardial infarction (MI) but increases the risk of bleeding. MIs and bleeds during the index hospitalization for PCI are known to negatively affect long-term outcomes. The impact of spontaneous bleeding occurring after discharge on long-term mortality is unknown. This study sought to examine, in a real-world cohort, the association between spontaneous major bleeding or MI after PCI and long-term mortality. We conducted a retrospective cohort study of patients ≥30 years of age who underwent a PCI between 1996 and 2008 in an integrated healthcare delivery system. We used extended Cox regression to examine the associations of spontaneous bleeding and MI with all-cause mortality, after adjustment for time-updated demographics, comorbidities, periprocedural events, and longitudinal medication exposure. Among 32,906 patients who had a PCI and survived the index hospitalization, 530 had bleeds and 991 had MIs between 7 and 365 days post-discharge. There were 4,048 deaths over a mean follow-up of 4.42 years. The crude annual death rate after a spontaneous bleed (9.5%) or MI (7.6%) was higher than among patients who experienced neither event (2.6%). Bleeding was associated with an increased rate of death (adjusted hazard ratio [HR]: 1.61, 95% confidence interval [CI]: 1.30 to 2.00), similar to that after an MI (HR: 1.91; 95% CI: 1.62 to 2.25). The association of bleeding with death remained significant after additional adjustment for the longitudinal use of antiplatelet agents. Spontaneous bleeding after a PCI was independently associated with higher long-term mortality, and conveyed a risk comparable to that of an MI during follow-up. This tradeoff between efficacy and safety bolsters the argument for personalizing antiplatelet therapy after PCI on the basis of the patient's long-term risk of both thrombotic and bleeding events.